Surgical procedures in cats in a teaching veterinary hospital (Research, Society and Development, 2022)
The aim of this article was to conduct a survey of surgical procedures performed on cats in a teaching veterinary hospital (TVH) for a period of seven months. Qualitative research was carried out, using percentage and numerical frequencies. In a veterinary teaching hospital, 92 cats submitted to surgeries were accompanied, and, 62 were females (67.39%; 62/92) and 30 males (32.61%; 30/92). Of the total cases, 61 were therapeutic surgical procedures (66.30%; 61/92), and 31 were elective surgeries (33.69%; 31/92). Of the elective surgeries, 22 were ovariohysterectomy (70.96%; 22/31) and nine were orchiectomies (29.03%; 9/31). Among therapeutic surgical procedures, the emergency surgeries were majority, representing 48 cases (78.68%; 48/61. The most frequent therapeutic surgery was ovariohysterectomy with 26 occurrences (42.62%; 26/61). The other surgical therapeutic procedures in order of frequency were: desobstruction urethral, fracture reduction, ocular bulb enucleation, incisional hernia correction, rectal prolapse correction and evisceration correction. There were three deaths, all in the postoperative period. The emergencies were highlighted and, among them, the most frequent surgery was ovariohysterectomy due to dystocic parturition, which may be linked to the use of contraceptives. In the veterinary clinical routine, there is a significant increase in feline patients. In this way, it is considered important that the feline species be the object of study in Brazil